2010
DOI: 10.1115/1.4000224
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Behavior of Stainless Steel 304L Including Strain Hardening, Prestraining, and Mean Stress Effects

Abstract: This paper discusses cyclic deformation and fatigue behaviors of stainless steel 304L and aluminum 7075-T6. Effects of loading sequence, mean strain or stress, and prestraining were investigated. The behavior of aluminum is shown not to be affected by preloading, whereas the behavior of stainless steel is greatly influenced by prior loading. Mean stress relaxation in strain control and ratcheting in load control and their influence on fatigue life are discussed. Some unusual mean strain test results are presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 21 publications
3
51
0
Order By: Relevance
“…However, this is an experimental observation and more test data is required to explain the thickness effect. In general, there are three different characteristics (short hardening, slight softening, and significant secondary hardening) under the cyclic behavior of AISI 304L base metal [3,20]. It is noted that the softening behavior of AISI 304L depends on the applied strain amplitude.…”
Section: Thickness Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this is an experimental observation and more test data is required to explain the thickness effect. In general, there are three different characteristics (short hardening, slight softening, and significant secondary hardening) under the cyclic behavior of AISI 304L base metal [3,20]. It is noted that the softening behavior of AISI 304L depends on the applied strain amplitude.…”
Section: Thickness Effectmentioning
confidence: 99%
“…This implies that changes in the strain ratio do not significantly affect the fatigue performance of a welded joint in low-cycle region. Many studies also demonstrated that an increased mean stress has more influence on the fatigue characteristics than the effect of the strain ratio in low-cycle regions [3,21]. cyclic softening compared to the tendency of R = −1.…”
Section: Strain Ratio Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 lists the description of the experimental fatigue data employed in this study. The data were gathered from EDF, its partners and the literature [11][12][13][14][15][16][17][18][19], which was obtained from standard specimens made of the 304L stainless steel as discussed in details in the corresponding references. It should be emphasized that all these tests are under constant amplitude fatigue loadings.…”
Section: Correlation Of Experimental Fatigue Data Using Equivalent Crmentioning
confidence: 99%
“…To determine the required parameters for the reliable and accurate prediction of fatigue life, the effect of this prior straining on the subsequent cyclic behavior and fatigue, with or without mean stress and strain, must be considered. Several previous works were interested in the prehardening effects on the fatigue life of metallic materials [1,2]; where, mean stress can be positive or negative during fatigue tests. Therefore, our objective here is to study the isolate effect of a prehardening in axial and shear direction on the fatigue at zero mean stress and/or strain.…”
Section: Introductionmentioning
confidence: 99%